2009
DOI: 10.1590/s1517-83822009000400035
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of genes required for anaerobic respiration to the virulence of Salmonella enterica serovar Gallinarum for chickens

Abstract: Salmonella enterica serovar Gallinarum (SG) is an intracellular pathogen of chickens. To survive, to invade and to multiply in the intestinal tract and intracellularly it depends on its ability to produce energy in anaerobic conditions. The fumarate reductase (frdABCD), dimethyl sulfoxide (DMSO)-trimethylamine N-oxide (TMAO) reductase (dmsABC), and nitrate reductase (narGHIJ) operons in Salmonella Typhimurium (STM) encode enzymes involved in anaerobic respiration to the electron acceptors fumarate, DMSO, TMAO,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The napA mutant of S . Typhimurium exhibited a considerable growth defect in the low-nitrate colonic lumen of mice [ 48 ]; by contrast, the highest mortality rates of chickens challenged with mutants of S. gallinarum were associated with mutations in napA and narG , and additional attenuations were induced by a mutation in frdA and double mutations in dmsA and torC [ 49 ]. The findings are consistent with our emapplot network of downregulation in napA , dmsA , torC , and narG after the mutation in yqiC that is associated with colonization and ETCs.…”
Section: Discussionmentioning
confidence: 99%
“…The napA mutant of S . Typhimurium exhibited a considerable growth defect in the low-nitrate colonic lumen of mice [ 48 ]; by contrast, the highest mortality rates of chickens challenged with mutants of S. gallinarum were associated with mutations in napA and narG , and additional attenuations were induced by a mutation in frdA and double mutations in dmsA and torC [ 49 ]. The findings are consistent with our emapplot network of downregulation in napA , dmsA , torC , and narG after the mutation in yqiC that is associated with colonization and ETCs.…”
Section: Discussionmentioning
confidence: 99%
“…An inactivated vaccine can be considered as a safer alternative to SG 9R. However, several reports have shown that inactivated SG vaccines are not sufficient to provide protection against salmonellosis and less cross-protective against other Salmonella species, such as Salmonella Pullorum (SP) or Salmonella Enteritidis (SE) because of the low cell-mediated immune response (11,12). Of the several inactivation methods available for vaccine development, inactivation by irradiation has been reported to enhance the induction of cell-mediated immunity for bacterial and viral vaccines (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic Enterobacteriaceae have evolved to use fumarate reductase, encoded by frdABCD genes, to grow under anaerobic conditions in vitro and in vivo (Iverson et al, 1999; Jones et al, 2007; Mercado-Lubo et al, 2008; Paiva et al, 2009). Interestingly, the S. Tm and pks + E. coli SP15 genomes encode the aspA gene (aspartate ammonia-lyase), which enable the conversion of the amino acid aspartate into fumarate (Nguyen et al, 2020; Nógrády et al, 2003) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The S. Tm and E. coli genomes encode an aspartate-ammonia lyase ( aspA ) which enables the conversion of the amino acid aspartate into fumarate, an alternative electron acceptor (Falzone et al, 1988). S. Tm predominantly uses the fumarate reductase encoded by frdABCD genes under anaerobic or hypoxic conditions for expansion through fumarate respiration in the host gut during early infection (Arguello et al, 2010; Jones et al, 2007; Mercado-Lubo et al, 2008; Paiva et al, 2009). However, the major source of fumarate during later stages of S. Tm intestinal infection, and whether aspartate-dependent fumarate respiration supports microbiota outgrowth by pathogenic Enterobacteriaceae in the inflamed gut remains unclear.…”
Section: Introductionmentioning
confidence: 99%